BIOMASS PRODUCTION AND NUTRIENT REQUIREMENT DURING RESTORATION OF A HOLM OAK COPPICE - LEONARDI, S; Rapp, M (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1990)
The restoration of a holm oak (Quercus ilex L.) coppice was studied during three years following a clear-cut. Leaf area rebuilding, above-ground biomass production and nutrient requirement are especially studied. The new produced above-ground biomass amounts respectively to 151, 913 and 2 161 g m-2, one, two and three years after clear-cut. Leaf area index, at the same ages, amounts respectively to 0,3-1,9 and 4,4 m2/m2. The last value is nearly the same as those of the 30 year old coppice stand (4,4 m2/m2). The biomass increment corresponds to a current yearly above-ground productivity of 165, 748 and 1 248 g m-2 of fresh material during these three years. The mean annual above-ground production, calculated over thirty years, only amounts to 800 g m-2. Concerning nutrients, it seems that the early years are characterized by a higher requirement of nitrogen, phosphorus and potassium in comparison to the mature stand. The needs for calcium start to be important only after the third year, with the reappearance of ``stems{''} and later trunks.
Keywords: biomass; coppice; NUTRIENT REQUIREMENT; STAND RESTORATION